Ethnographic research in immigrant-specific drug abuse recovery houses. Issue 1 (2nd January 2018) - Pagano, Anna; Lee, Juliet P.; García, Victor; Recarte, Carlos
ABSTRACT: Access to study populations is a major concern for drug use and treatment researchers. Spaces related to drug use and treatment have varying levels of researcher accessibility based on several issues, including legality, public versus private settings, and insider/outsider status. Ethnographic research methods are indispensable for gaining and maintaining access to hidden or "hard-to-reach" populations. Here, we discuss our long-term ethnographic research on drug abuse recovery houses created by and for Latino migrants and immigrants in Northern California. We take our field work experiences as a case study to examine the problem of researcher access and how ethnographic strategies can be successfully applied to address it, focusing especially on issues of entrée, building rapport, and navigating field-specific challenges related to legality, public/private settings, and insider/outsider status. We conclude that continued funding support for ethnography is essential for promoting health disparities research focused on diverse populations in recovery from substance use disorders.